Evaluation of three MALDI‐TOF mass spectrometry libraries for the identification of filamentous fungi in three clinical microbiology laboratories in Manitoba, Canada. Issue 10 (2nd July 2018) - Stein, Markus; Tran, Vanessa; Nichol, Kimberly A.; Lagacé‐Wiens, Philippe; Pieroni, Peter; Adam, Heather J.; Turenne, Christine; Walkty, Andrew J.; Normand, Anne‐Cécile; Hendrickx, Marijke; Piarroux, Renaud; Karlowsky, James A.
Summary: Matrix‐assisted laser desorption ionisation‐time of flight mass spectrometry (MALDI‐TOF MS) is commonly used by clinical microbiology laboratories to identify bacterial pathogens and yeasts, but not for the identification of moulds. Recent progress in extraction protocols and the composition of comparative libraries support potential application of MALDI‐TOF MS for mould identification in clinical microbiology laboratories. We evaluated the performance of the Bruker Microflex™ MALDI‐TOF MS instrument (Billerica, MA, USA) to identify clinical isolates and reference strains of moulds using 3 libraries, the Bruker mould library, the National Institutes of Health (NIH) library and the Mass Spectrometry Identification (MSI) online library, and compared those results to conventional (morphological) and molecular (18S/ITS; gold standard) identification methods. All 3 libraries demonstrated greater accuracy in genus identification (≥94.9%) than conventional methods (86.4%). MALDI‐TOF MS identified 73.3% of isolates to species level compared to only 31.7% by conventional methods. The MSI library demonstrated the highest rate of species‐level identification (72.0%) compared to NIH (19.5%) and Bruker (13.6%) libraries. Greater than 20% of moulds remained unidentified to species level by all 3 MALDI‐TOF MS libraries primarily because of library limitations or imperfect spectra. The overall identification rate of each MALDI‐TOF MS library depended on the number of species and the number of spectra representing each species in the library.